Inverse isolate domination on four–regular graphs withgirth 3 and girth 4 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Let G be non-trivial graph. A subset S of the vertex set V(G) of a graph G is called a isolatedominating set of G if every vertex in V – S is adjacent to a vertex in S such that δ(<